PENGARUH MOTIVASI DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR SISWA - Armisah Agustinah; Irawan Suntoro; Yunisca Nurmalisa (FKIP Unila, 2012)
The objective of this research was to explain the influence of motivations and learning discipline toward civic education achivement of the second grade student’s in add semester on civic education subject in SMK YAPEMA Gadingrejo in academic 2011/2012. The main data collecting technique used questionnaire and interview suporting technique was literature review. The variables of this research were the influence of motivation and student’s learning discipline toward learning achivement. Data analysis used in this research was regression analysis. Based on the result of the research, it was gotten that there was significant influence of motivation and learning discipline toward student’s achievement on civic education subject in SMK YAPEMA Gadingrejo in academic year 2011/2012. It mean better motivation and learning discipline of the student better the student’s learning achievement, and was worse the motivation and learning achievement.Keywords: motivation, discipline , learning achievement, civic education